2013
DOI: 10.1159/000346572
|View full text |Cite
|
Sign up to set email alerts
|

Acrodermatitis Continua of Hallopeau Is a Clinical Phenotype of DITRA: Evidence that It Is a Variant of Pustular Psoriasis

Abstract: Acrodermatitis continua of Hallopeau (ACH) is a rare, chronic, sterile, pustular eruption that predominantly affects the fingertips with nail involvement. While some consider ACH a distinct entity, many believe it to be a variant of pustular psoriasis, especially as cases of ACH progressing to generalized pustular psoriasis (GPP) have been reported. Recently, recessively inherited mutations in the IL36RN gene, which encodes interleukin-36 receptor antagonist (IL-36Ra), have been demonstrated to be the cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 11 publications
2
52
0
5
Order By: Relevance
“…Moreover, anakinra was recently successfully used in a case of DITRA syndrome in an infant [10] as well as in 3 cases [11,12] of generalized pustular psoriasis, one of them carrying a mutation of the IL-36RN gene [12]. IL-36 RN mutations can be found in patients with generalized pustular psoriasis [10,11] and in rare patients with ACH [12,13,14,15]. It has been hypothesized that such mutations could be associated with the response of generalized pustular psoriasis [12] or ACH [9] to anakinra [13,14], but this has not been demonstrated [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, anakinra was recently successfully used in a case of DITRA syndrome in an infant [10] as well as in 3 cases [11,12] of generalized pustular psoriasis, one of them carrying a mutation of the IL-36RN gene [12]. IL-36 RN mutations can be found in patients with generalized pustular psoriasis [10,11] and in rare patients with ACH [12,13,14,15]. It has been hypothesized that such mutations could be associated with the response of generalized pustular psoriasis [12] or ACH [9] to anakinra [13,14], but this has not been demonstrated [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the function loss of IL-36RN (previously known as IL-1F5) implicates that GPP is caused by innate immune dysregulation in this severe episodic inflammatory disease. Therefore, taking IL-1 as a potential target for therapeutic intervention might cure the disease [20,21]. In order to find a better treatment for IH, more work should be continuously done to find the gene mutation of IH.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians unfamiliar with the disease can misdiagnose it as a chronic infection through identification of commensals (such as M. fortuitum ) on culture specimens. Reports of a Lebanese family with a common IL-36RN mutation presenting as both ACH and GPP raises questions as to the epigenetic or environmental cues that may result in different phenotypes [2], progression from one to the other [5], or manifestations of both, as seen in our case. It is also unclear why, if the conditions are related, such contrasting responses to treatment are seen within the same individual and why long-term remission often remains elusive [6].…”
Section: Discussionmentioning
confidence: 93%
“…ACH is a chronic, recalcitrant disease with a predisposition to elderly females [1], is considered an acral variant of pustular psoriasis [2], and shares a common pathogenesis with DITRA (deficiency in interleukin-1 receptor antagonist) [2,3,4]. Physicians unfamiliar with the disease can misdiagnose it as a chronic infection through identification of commensals (such as M. fortuitum ) on culture specimens.…”
Section: Discussionmentioning
confidence: 99%